PENGARUH TEKNIK MIND MAPPING BERBASIS MODEL PROBLEM BASED LEARNING TERHADAPKETERAMPILANMENULIS KARANGAN NARASI EKSPOSITORIS SISWA KELAS X SMA NEGERI 8 PADANG - Zuraida Zuraida; Dwi Mutia Chan; Najmi Hayati (STKIP Pesisir Selatan, 2023)
The purpose of this research (1) the skills of writing expository narrative essays for class X students of SMA Negeri 8 Padang before applying the mind mapping technique based on problem based learning models.(2) The skills of writing expository narrative essays for class X students of SMA Negeri 8 Padang after applying the mind mapping technique based on problem based learning models.(3) Analyzing the effect of applying mind mapping techniques based on problem based learning models on the skills of writing expository narrative essays for class X students of SMA Negeri 8 Padang. This type of research is quantitative.The research method applied is the experimental method. The research design is a pre-test and post-test group design.The procedure of this research were (1) pretest stage, (2) treatment, (3) posttest.The research sample was 30 class X4 students of SMA Negeri 8 Padang.The instrument used in this study is the performance test.There are three data collection procedures in this study, (1) do a pretest, data collection procedures before applying problem based learning mind mapping techniques,(2) carry out the learning process by applying mind mapping techniques based on problem based learning models,(3) held a posttest. Based on the results of data analysis and discussion, the following conclusions are obtained (1) The skills of writing expository narrative essays for class X4 students of SMA Negeri 8 Padang before being applied to the problem-based learning model-based mind mapping technique were in the